Receptacle Structure of Termite Fungus (Termitomyces) - ศรีไชยวงศ์ เมธี; กลิ่นหอม อุษา; บุตรสาทร พาป้อง ขวัญเรือน (KKU Science Journal, 2013)
The receptacle is a structure which connects between pseudorhiza and fungus comb.The genus Termitomyces has an important structure which is called receptacle. The detail of receptacle structure has not been reported. The aim of this study to examine the structure of receptacle in genus Termitomyces. One hundred and nineteen samples of Termitomyces were collected from dry dipterocarp and community forests in Northeast of Thailand. The result shows that there were 5 types of receptacle including rod shape, white radish shape, taro shape, lace shape and knob shape.